2021
DOI: 10.1108/ecam-06-2020-0399
|View full text |Cite
|
Sign up to set email alerts
|

The motivation of operatives in small construction firms towards health and safety – A conceptual framework

Abstract: PurposeHealth and safety in small construction firms is often neglected by owners leading to poor health and safety performance and unacceptably high fatality and injury rates. A body of knowledge has established significant links between the motivational behaviours of operatives towards health and safety. Motivation is also considered as a key tool for improving operative productivity as when operatives experience safe worksites, they can carry out their work in a more productive manner. The purpose of this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
0
5
0
2
Order By: Relevance
“…These bene ts include cost savings resulting from fewer accidents and legal disputes, and increased project quality (Howarth & Watson, 2010), which could partly lead to CS. Also, the positive signi cant mediating effect observed in this study could be due to the improvement in HSP in projects adopting GCPs as reported by Khan et al (2021). Furthermore, they may have been a change in the way GCPs are been adopted as the adoption of the "prevention through design concept" has become increasingly popular (Zhou et al, 2015).…”
Section: Discussion Of Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…These bene ts include cost savings resulting from fewer accidents and legal disputes, and increased project quality (Howarth & Watson, 2010), which could partly lead to CS. Also, the positive signi cant mediating effect observed in this study could be due to the improvement in HSP in projects adopting GCPs as reported by Khan et al (2021). Furthermore, they may have been a change in the way GCPs are been adopted as the adoption of the "prevention through design concept" has become increasingly popular (Zhou et al, 2015).…”
Section: Discussion Of Resultsmentioning
confidence: 60%
“…As such, many green building rating tools such as LEED have included credits for the prevention of safety issues through design (Karakhan & Gambatese, 2017). In view of the increased quest and measures taken towards HSP in projects that adopt GCPs, Khan et al (2021) report that there has been signi cant improvement in the HSP during CCP adoption. Yusliza et al (2020) report that CCP are largely expected to lead to HSP.…”
Section: Mediating Effect Of Health and Safety Performance On The Relationship Between Green Construction Practices And Client Satisfactimentioning
confidence: 99%
“…Los factores que impactan en la seguridad y salud en el trabajo son: la informalidad, las regulaciones sobre el embarazo de mujeres, nuevas tecnologías, nuevos tipos de trabajo, incluido el teletrabajo, envejecimiento de la población [24]. Otros factores que considera [25] son extrínsecos como: la formación, las condiciones de trabajo, el compromiso de la dirección, el sistema de gestión de SST con sus políticas y procedimientos de seguridad y salud; o intrínsecos de las personas como son: factores psicológicos, comportamiento, actitudes y satisfacción. Estos son parte integral cuando se abordan los sistemas de gestión de seguridad y salud en el trabajo La cultura organizacional en los sistemas de gestión tiene una estrecha relación con los principios de calidad como son el liderazgo, compromiso de las personas y mejora continua; por lo cual, el componente humano es un factor clave en la aplicación de las normas ISO u otros estándares de gestión de la SST.…”
Section: Resultsunclassified
“…According to studies, motivation contributes not only to competence and endurance in CPR but also to appropriate interventions and effective CPR [16][17][18]. High-quality CPR improves patient survival [19], and work motivation leads to high-quality performance and better clinical outcomes [20,21]. The assumption that motivation affects rescuers' performance and CPR outcomes suggests that the selection of highmotivation rescuers for CPR is necessary [18,22].…”
Section: : Backgroundmentioning
confidence: 99%